Behavioral Changes Over Time Following Ayahuasca Exposure in Zebrafish - Savoldi, Robson; Polari, Daniel; Pinheiro-da-Silva, Jaquelinne; Silva, Priscila F.; Lobao-Soares, Bruno; Yonamine, Mauricio; Freire, Fulvio A. M.; Luchiari, Ana C. (Frontiers in Behavioral Neuroscience, 2017)
The combined infusion of Banisteriopsis caapis stem and Psychotria viridis leaves, known as ayahuasca, has been used for centuries by indigenous tribes. The infusion is rich in N, N-dimethyltryptamine (DMT) and monoamine oxidase inhibitors (MAOIs), with properties similar to those of serotonin. Despite substantial progress in the development of new drugs to treat anxiety and depression, current treatments have several limitations. Alternative drugs, such as ayahuasca, may shed light on these disorders. Here, we present time-course behavioral changes induced by ayahuasca in zebrafish, as first step toward establishing an ideal concentration for pre-clinical evaluations. We exposed adult zebrafish to 5 concentrations of the ayahuasca infusion: 0ml/L (control), 0.1ml/L, 0.5ml/L, 1ml/L and 3ml/L (n=14 each group), and behavior was recorded for 60 min. We evaluated swimming speed, distance traveled, freezing and bottom dwelling every min for 60 min. Swimming speed and distance traveled decreased with an increase in ayahuasca concentration while freezing increased with 1 and 3ml/L. Bottom dwelling increased with 1 and 3 ml/L, but declined with 0.1ml/L. Our data suggest that small amounts of ayahuasca do not affect locomotion and reduce anxiety-like behavior in zebrafish, while increased doses of the drug lead to crescent anxiogenic effects. We conclude that the temporal analysis of zebrafish behavior is a sensitive method for the study of ayahuasca-induced functional changes in the vertebrate brain.